Colorimetric Gas Sensing Washable Threads for Smart Textiles - Owyeung, Rachel E. (Sci Rep, 2019)
A fabrication method for a stable entrapment of optically responsive dyes on a thread substrate is proposed to move towards a detection system that can be integrated into clothing. We use the dyes 5,10,15,20-Tetraphenyl-21H,23H-porphine manganese(III) chloride (MnTPP), methyl red (MR), and bromothymol blue (BTB), for a proof-of-concept. Our optical approach utilizes a smartphone to extract and track changes in the red (R), green (G) and blue (B) channel of the acquired images of the thread to detect the presence of an analyte. We demonstrate sensing of 50–1000 ppm of vapors of ammonia and hydrogen chloride, components commonly found in cleaning supplies, fertilizer, and the production of materials, as well as dissolved gas sensing of ammonia. The devices are shown to be stable over time and with agitation in a centrifuge. This is attributed to the unique dual step fabrication process that entraps the dye in a stable manner. The facile fabrication of colorimetric gas sensing washable threads is ideal for the next generation of smart textile and intelligent clothing.